FACTORS ASSOCIATED WITH WORKPLACE ACCIDENTS AMONG HEALTH WORKERS AT THE UPTD UEESI COMMUNITY HEALTH CENTER, EAST KOLAKA REGENCY, 2024: FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN KERJA PADA PETUGAS KESEHATAN UPTD PUSKESMAS UEESI KABUPATEN KOLAKA TIMUR KOLAKA TIMUR TAHUN 2024 - Azhar Jamil, Azhar Jamil; Achmad R. Muttaqien Al-Maidin; Andi Alim (Homes Journal = Hospital Management Studies Journal, 2025)
Background: Occupational health refers to a series of efforts undertaken by an organization to maintain and enhance the physical, mental, and social well-being of its employees. In primary healthcare settings such as community health centers (puskesmas), workplace accidents are often attributed to human error, including a lack of attentiveness while performing tasks and the failure to use personal protective equipment properly. This study aims to examine the influence of the work environment, knowledge level, attitude, and the implementation of occupational health and safety (OHS) regulations on the performance and safety of healthcare workers at the UPTD Puskesmas Ueesi, East Kolaka Regency, in 2024. Method: A cross-sectional study design was employed. Bivariate analysis using the Mann-Whitney test was conducted to assess whether there is a statistically significant association between variables measured on an ordinal scale Result: The analysis revealed no statistically significant association between variables such as length of service, knowledge level, attitude, or working environment and the occurrence of workplace accidents. The Mann-Whitney test yielded an Asymp. Sig. (2-tailed) value greater than 0.05, indicating no meaningful relationship between the variables examined in this study. Conclusion: The findings suggest that there is no significant relationship between the analyzed variables and the incidence of workplace accidents among healthcare workers at UPTD Puskesmas Ueesi. These results imply the possible presence of other contributing factors not examined in this study, warranting further research to gain a more comprehensive understanding.